The influence of halal label, price, and brand image on cosmetic product purchase decisions among female students at FEBI UIN KHAS Jember - Musaidah, Ahlam; Ahmadiono, Ahmadiono; Masrohatin, Siti (Journal of Islamic Economics Lariba, 2024)
IntroductionHumans have two primary needs: basic and secondary needs. Women in particular have distinct needs related to their appearance. Cosmetics serve not only to beautify but also to care for the body from head to toe. Many women incorporate cosmetics into their daily routines and use them from morning to night.ObjectivesThe objective of this study is to determine the influence of halal label, price, and brand image on purchasing decisions for cosmetics among female students at UIN KHAS Jember.MethodThis quantitative research employed multiple linear regression analysis. The sample size was determined using Slovin's formula and data were collected through questionnaires distributed to a selected sample of students. The study analyzed the validity, reliability, and classical assumption tests (normality, heteroskedasticity, and multicollinearity) and used multiple linear regression to assess the impact of the independent variables (halal label, price, and brand image) on the dependent variable (purchase decision).ResultsThe findings reveal that halal label and brand image positively influence the purchasing decisions of cosmetic products. These results indicate that students at UIN KHAS Jember consider halal label, price, and brand image as determinants when making cosmetic purchase decisions.ImplicationsThis study highlights the importance of halal labeling in reducing consumer doubts about product halal status, particularly for Muslim consumers who use cosmetics daily. The positive impact of brand image suggests that students are influenced by the reputation and perceived quality of cosmetic brands. These findings also suggest that competitive pricing strategies can significantly affect purchase decisions.Originality/NoveltyThis study provides insights into the factors influencing cosmetic purchase decisions among Muslim students, emphasizing the role of halal certification. This study contributes to the understanding of consumer behavior in the context of halal products, which is critical for marketers targeting Muslim consumers.